Tiedmann 2013 Solifluction Lobes as Potential Sediment Contributors to Linnévatnet Spitsbergen Svalbard - ACADIS Community Support (Arctic Data Center, 2013)
Abstract: As global changes become more pronounced, arctic regions are increasingly significant in climate studies due to their sensitivity and rapid response to the environment. Svalbard, an arctic archipelago located at 78°N, provides ideal subjects for studying climate history and the impacts of climate change given the abundance of glaciers and continuous permafrost. This study was conducted in western Spitsbergen, Svalbard, as part of a larger project examining climate and sedimentation in the Linnédalen glacio-fluvial-lacustrine system. Sedimentation records in such environments can serve as important proxies of past climate as well as indicators of current climate change, particularly in the preservation of varves. However, in order to interpret such sedimentation patterns, both primary and secondary sources of sediment must be characterized. Soliflucting lobes of relict marine terraces around Linnévatnet were examined and compared to lake cores to identify their potential sediment contribution. This potential input was investigated by mapping the shoreline, deploying short-term sediment traps for the summer 2012 field season, collecting 13 source grab samples, and extracting 5 lake cores. Sieve and laser grain-size analyses were performed on the source samples to further characterize the potential sources. The mineralogical compositions of the lake cores and source samples were analyzed using X-ray diffraction. The grain-size results point to the common original glacio-marine-fjord deposition in this dynamic setting with many sediment inputs. The similar grain-size distributions seen in solifluction samples not only reveal the valley-wide feature of the absence of medium sand(1 to 2φor 0.5 to 0.25 mm), but also help explain the lack of mineralogical variation among the clay fractions of source samples. Variations among the clay fraction of source samples (the fraction potentially reaching lake cores) are observed in the relative abundances of chlorite and illite and appear to reflect proximal bedrock sources. However, these differences do not visibly translate to the 5 lake cores, and all cores maintain similar chlorite:illite ratios, preventing a quantitative assessment of how much each potential source is contributing to the lake cores or whether the solifluction sources are significantly impacting varve analyses.